Application of COBIT 2019 Design Factors in Strengthening IT Governance in the Palm Oil Plantation Sector - Joe Yuan Mambu; Reynoldus Andrias Sahulata; Sherley Tambanua; Jacklin Pangau (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Rapid technological developments have changed the process of searching for boarding houses, which has been done manually through brochures, pamphlets, or banners. These conventional methods are considered inefficient because of their limited reach and the time required, especially for prospective tenants from outside the area. This study designs and develops a mobile-based e-boarding house application with features such as searching, booking, and digital payments, using the Rapid Application Development (RAD) methodology. This application makes it easier for users to find boarding houses that suit their wishes while making it easier for boarding house owners to manage room availability, tenant data, and payment history in a structured manner. The test results show that the e-boarding house application runs optimally without technical constraints and is effective in meeting user needs. By providing digital solutions, this application can increase the efficiency of searching and managing boarding houses, so that the process becomes faster, more practical, and more modern. Implementing this system provides significant benefits for prospective tenants and boarding house owners, namely increasing accessibility and management in the boarding house industry